2006
DOI: 10.1176/appi.ajp.163.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral Prefrontal Cortex Activation and Attentional Bias in Response to Angry Faces in Adolescents With Generalized Anxiety Disorder

Abstract: Objective: While adolescent anxiety disorders represent prevalent, debilitating conditions, few studies explore their brain physiology. Using event-related functional MRI (fMRI) and a behavioral measure of attention to angry faces, we evaluated differences in response between healthy adolescents and adolescents with generalized anxiety disorder (GAD). Method:In the primary trials of interest, 18 adolescents with GAD and 15 comparisons of equivalent age/gender/IQ viewed angry/neutral face pairs during fMRI acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
273
5
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(309 citation statements)
references
References 13 publications
21
273
5
10
Order By: Relevance
“…Youth who demonstrate greater activation in vlPFC and dlPFC prior to treatment may be more effective in regulation of responses to threatening stimuli and thus able to achieve greater therapeutic gains. In support, greater vlPFC activation has been observed in anxious youth compared with healthy controls during fear processing (McClure et al, 2007b), with some evidence that vlPFC activation is negatively related to anxiety severity (Monk et al, 2006) and increases following treatment for anxiety (Maslowsky et al, 2010), possibly reflecting improvements in emotion regulation. Another possibility, however, is that youth with greater vlPFC and dlPFC activation prior to treatment require increased effort to regulate emotions, which may become more automatic following treatment and contribute to greater improvement in symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…Youth who demonstrate greater activation in vlPFC and dlPFC prior to treatment may be more effective in regulation of responses to threatening stimuli and thus able to achieve greater therapeutic gains. In support, greater vlPFC activation has been observed in anxious youth compared with healthy controls during fear processing (McClure et al, 2007b), with some evidence that vlPFC activation is negatively related to anxiety severity (Monk et al, 2006) and increases following treatment for anxiety (Maslowsky et al, 2010), possibly reflecting improvements in emotion regulation. Another possibility, however, is that youth with greater vlPFC and dlPFC activation prior to treatment require increased effort to regulate emotions, which may become more automatic following treatment and contribute to greater improvement in symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…The few adult studies that have examined correlations between amygdala activity and anxiety severity have yielded mixed findings, with some showing evidence of significant positive relationships (35) and others demonstrating non-significant associations between the two (36). Two recent studies found amygdala activation to relate to one, but not a second, measure of anxious symptoms Similar inconsistency is evident in studies of youth; whereas some recent research in a clinical adolescent sample yielded no evidence of a relationship between symptom severity and amygdala activation (37), findings in another study focused on a healthy sample point to a linear association (11). Patterns of correlation appear to vary depending on a number of factors, including the sample under study and the task used to elicit amygdala activation; clearly further study that carefully controls such factors is needed to elucidate the relationship between pre-treatment symptomatology and amygdala activation.…”
Section: Discussionmentioning
confidence: 96%
“…A study on anxious youth using selective imaging of the amygdala showed that patients showed greater response to threat-related facial expressions and increased amygdala activation and abnormal ventral PFC responses. These neural abnormalities may be responsible for regulatory processes of anxietyrelated behaviours (4,31). Only the role of GABA receptors in the mPFC has been evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…GABA is the main inhibitory neurotransmitter of the brain acting through different receptor sites called GABA A , GABA B and GABA C (4). GABAergic neurons are one of the most important components prevalent in all areas of the brain and its neurotransmission is vital for brain function (5).…”
Section: Introductionmentioning
confidence: 99%